Hubungan Gejala Penyakit Covid-19 Dengan Status Vaksinasi Pada Pasien Isolasi Terpusat di Puskesmas Gayaman Kabupaten Mojokerto Periode Januari - Agustus Tahun 2021 - Arinda Rindang Nastietie; Eka Aris Adiatma; Titan Dhea Anggraini; Carolin Carolin; Gembong Nuswanto (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
COVID-19 is one of the newly discovered diseases, so prevention methods are still limited. There are various ways that the government has taken to deal with COVID-19 in Indonesia, including urging its citizens to stay at home, promoting wearing masks and washing hands when doing activities outside the home, closing all access that can lead to crowds, changing the education system, employment, etc. as well as online learning, and the last is a vaccination program to reduce the symptoms of COVID-19 if infected. The vaccination is expected to reduce morbidity and mortality from COVID-19, achieve herd immunity to prevent transmission and protect public health. Seeing from the description that has been described above, the researchers are interested in conducting research related to the relationship between symptoms of COVID-19 disease and vaccination status in centrally isolated patients at the Gayaman Public Health Center, Mojokerto Regency. This research is an analytic observational study using a cross sectional research design. The data analysis used in this research is Chi-Square. From the results of the Chi Square test and the contingency coefficient, a p-value of 0.342 (> 0.05) is obtained, so it can be interpreted that there is no relationship between symptoms of Covid-19 disease and vaccination status in centralized isolated patients at the Gayaman Health Center.